How Artistic Research Can Assist in Answering Audience Engagement Questions? - Balevičiūtė, Ramunė; Sokolovaitė, Milda (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English] There is an increasing interest in audience engagement and the possibilities of its research in contemporary performance practice. One of the possibilities that can be used in conducting such a study is a practice-led type of research, commonly known as artistic research. The distinguishing quality of this type of research, which has been finding its place in academia throughout the last few decades, is that it uses artistic practice to generate new knowledge. This article analyzes the possibilities of such research from the point of view of the aesthetics of performativity, which focuses on works that explore audience engagement rather than representation. While analyzing examples of performance and theater art works, it tackles the issue of how artistic research can assist in answering audience engagement questions.